Properti Psikometri Skala Identitas Nasional: Menggunakan Rasch Model - Afifah, Sarah; Widiatmoko, Catur (Universitas Muhammadiyah Metro, 2024)
The purpose of this study is to determine the quality of the instrument and the quality of the national identity scale items using the Rasch model analysis approach. To determine the quality of the national identity scale items for the population analyzed using the Rasch model, namely the item analysis approach. This study is a type of quantitative research. The scale developed is a national identity scale compiled based on Ashmore's collective identity theory. The research subjects successfully collected in this study amounted to N = 503. Based on the analysis using the Rasch model, the national identity scale instrument is reliable and valid. In terms of items, there are several national identity scale items that need to be discarded and revised. Of the 39 national identity scale items, 23 items were accepted, 7 items were replaced/discarded, and 9 items needed to be revised in terms of item difficulty. The Self-Categorization element is the element that has the most items discarded and revised so it needs to be considered in compiling the items.